RESEARCH The effect of gestational age on mitochondrial properties of the mouse placenta - Lucy A Bartho; Joshua J Fisher; Sarah L Walton; Anthony V Perkins; James S M Cuffe (Bioscientifica, 2022)
Mitochondria are organelles within the cell that generate energy, which is essential to the developing placenta. As the placenta approaches term, organelles such as mitochondria and the endoplasmic reticulum adapt to cellular stressors (e.g. oxidative stress and fluctuations in oxygen concentration) which are likely to result in the progressive decline of tissue function, known as placental ageing. This ageing phenotype may induce cellular senescence, a process whereby the cell is no longer proliferating, yet remains metabolically active. Mitochondria, endoplasmic reticulum and senescent processes are still poorly understood in the developing placenta. Therefore, a rodent ontogeny model was used to measure genes and proteins involved in mitochondrial biogenesis, antioxidant function, electron transport chain, mitophagy, dynamics and unfolded protein response in the placenta. CD-1 mouse placental samples were collected at embryonic day (E)12.5, E14.5, E16.5 and E18.5 of pregnancy for gene and protein analysis via qPCR, protein assays and Western blotting. Mitochondrial content, SDHB (complex II) and MFN2 (mitochondrial fusion) proteins were all increased throughout pregnancy, while citrate synthase activity/mitochondrial content, Tfam, Sirt3, Mfn1, TOMM20 (mitochondrial biogenesis and dynamics); Tp53 (senescence); Eif2ak3, Eif4g1 (endoplasmic reticulum stress); NDUFB8, UQCRC2, ATP5A (electron transport chain sub-complexes) were decreased at E18.5, compared to E12.5. Overall, mitochondria undergo changes in response to gestational progression and pathways associated with cellular ageing to facilitate adaptions in a healthy pregnancy. This data holds great promise that mitochondrial markers across pregnancy may help to establish when a placenta is ageing inappropriately.